Exploring the perceptions and practices of faraid (islamic inheritance): insights among muslim families in Padang Terap / Mohamad Zaim Isamail, Nurul Afifah Abdul Mulup, Husnizam Hosin, Munawar Rizki Jailani and Nur Aeisyah Mohamad Zaidi - Isamail, Mohamad Zaim; Abdul Mulup, Nurul Afifah; Hosin, Husnizam; Jailani, Munawar Rizki; Mohamad Zaidi, Nur Aeisyah (UiTM Cawangan Johor, 2025)
Faraid, commonly known as the Islamic inheritance system, is a legal framework based on Islamic laws. Its primary goal is to protect family members' rights in matters involving the assets of deceased individuals. This study rigorously examined the intricate subject of Faraid, known as Islamic inheritance, by analysing the beliefs and behaviors of Muslim people in Padang Terap. This research investigation is based on three primary objectives. First, it examined the current perceptions and practices of the targeted community regarding Faraid. Second, it identified and explored the factors contributing to the lack of knowledge about Faraid among Muslim communities in the Padang Terap. Lastly, it investigated the frequency of family disputes related to Faraid within the study population and the underlying causes of these disputes. This research project employed a quantitative methodology that sent an online questionnaire through a simple and random sampling approach. The data collected was evaluated using SPSS version 29, providing researchers with a comprehensive understanding of the dynamics surrounding Faraid in the selected community. By addressing these specific goals, this research seeks to enhance the understanding of Islamic inheritance and increase awareness of the difficulties faced by Muslim households in the Padang Terap.